A three-component double-reaction hydrogel material, preparation method and application thereof

By using three-component dual-react hydrogel material, it is formed by cross-linking using Knoevenagel condensation reaction and Michael addition reaction, the problem of degradation of existing hydrogel materials in the water environment is solved, the long-term residence of the hydrogel and the improvement of cell survival rate are achieved, and the therapeutic effect of cell transplantation is improved.

CN119119710BActive Publication Date: 2025-03-18CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411598393.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-18
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

Existing injectable hydrogel materials exchange kinetics in aqueous environments faster, resulting in degradation in a short period of time and lack of long-term stable performance, limiting the therapeutic effect of cell transplantation.

Method used

The three-component bireacterial hydrogel material is formed by cross-linking of polymers containing benzaldehyde functional groups, polymers containing cyanoalkyl acid ester functional groups and compounds containing sulfhydryl groups and carboxyl groups through Knoevenagel condensation reaction and Michael addition reaction, so as to achieve on-demand regulation of mechanical properties.

Benefits of technology

This hydrogel material has a fast gel formation speed and good self-healing and shear thinning. It can protect cells during injection and achieve long-term stay in situ, improving the therapeutic effect of cell transplantation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119710B_ABST
    Figure CN119119710B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of material science and technology, and in particular, relates to a three-component dual-reaction hydrogel material, a preparation method and application thereof. The three-component dual-reaction hydrogel provided by the present invention is a hydrogel material cross-linked by dynamic chemical bonds based on a C=C double bond formed by a Knoevenagel condensation reaction and pH responsiveness induced by thiol and carboxyl compounds and Michael addition reaction, and has the advantages of mild preparation conditions, fast gelation speed, in-situ adjustment of the mechanical properties of the hydrogel as needed after injection to achieve long-term retention of the hydrogel, and improved therapeutic effects of cell transplantation, so that the three-component dual-reaction hydrogel with rapid gelation and in-situ adjustment of the mechanical properties of the hydrogel as needed can be used as a cell transplantation treatment carrier in the field of biomedical materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material science and technology, and in particular relates to a three-component double-reaction hydrogel material, a preparation method and application thereof. Background Art

[0002] Cell transplantation therapy has great potential in reversing currently incurable diseases and regenerating tissues. However, this treatment approach has so far only achieved minor clinical success in hematopoietic stem cell transplantation. The main barriers limiting the clinical translation of cell transplantation include low cell survival, cell aggregation, and poor cell integration into host tissues. Regardless of tissue type, the vast majority of transplanted cells die, with only a few surviving cells remaining at the injection site. Although surviving cells are able to proliferate, most transplanted cells fail to properly integrate into host tissues and contribute to functional recovery. Combining cells with biomaterials provides a way to address the challenges of cell survival, migration, and integration. Biomaterials can influence cell behavior in vitro and in vivo, and tailoring the mechanical and biochemical properties of biomaterials can affect the fate of transplanted cells. Therefore, the combination of advanced material design and cell biology is key to improving the efficacy of cell transplantation.

[0003] Hydrogel materials are high-water-content materials formed by swelling of insoluble three-dimensional polymer networks in water, which can mimic the environment of the extracellular matrix. Due to the dynamic nature of the cross-linking points, hydrogels cross-linked by dynamic bonds or dynamic interactions have the properties of shear thinning and self-healing. Such hydrogels can inject the encapsulated cells into the target site by minimally invasive injection, and can protect the internal transplanted cells from shear damage during the injection process through the shear thinning property, thereby improving the survival rate of the cells. After injection, the hydrogel material can achieve self-healing. The complete hydrogel can improve the retention and proliferation of cells and promote the migration and integration of cells into tissues. Therefore, injectable hydrogels are one of the ideal cell transplantation carrier materials. However, injectable hydrogels as carrier materials also have certain problems. Since the cross-linking points are dynamic bonds or dynamic interactions, their exchange kinetics in the water environment are fast, the hydrogel material will degrade in a short time, lack long-term stability, and the cell scaffold will collapse in a short time, which seriously limits the therapeutic effect of cell transplantation.

[0004] Therefore, in response to the above problems, it is urgent to develop an injectable hydrogel material that is both injectable and has good mechanical properties and stability. The developed hydrogel can not only protect the therapeutic cells and deliver them to the target location by injection, but also achieve mechanical strength and stability regulation in situ to meet the treatment needs. This is one of the problems that many researchers in this field need to solve urgently.

[0005] The most commonly used method for preparing injectable hydrogel materials with both injectability and good mechanical properties and stability is to develop double-network or double-crosslinked hydrogel materials. The first network is prepared by mixing polymers that can form dynamic bonds or dynamic interaction crosslinks. The hydrogel has the dynamic properties of injectability and self-healing, which can protect the encapsulated transplanted cells from shear damage during the injection process and achieve self-healing in situ. The second network is formed on the basis of the first network. By introducing responsive groups on the polymer chains of the first network in advance or dissolving the responsive polymers in the first network in advance, new crosslinks are formed in situ in response to corresponding stimuli (heat, light, pH, etc.) in situ, and double-crosslinked or double-network hydrogels are prepared to enhance mechanical properties and stability, improve the retention of injectable hydrogels for cell transplantation carriers in situ, and improve the therapeutic effect of cell transplantation.

[0006] However, whether it is a double network or a double cross-linked hydrogel material, the formation of the second network or the second cross-link requires the design of a specific polymer structure, which is relatively complex and costly; and some specific response methods such as ultraviolet light, temperature, etc. will bring certain side effects, which may cause inflammation, and the operation is also more complicated, causing inconvenience. Summary of the invention

[0007] In view of this, the technical problem to be solved by the present invention is to provide a three-component dual-reaction hydrogel material, a preparation method and application thereof. The hydrogel material is used as a cell transplantation carrier, which can not only protect the encapsulated cells during the injection process and improve the survival of the cells, but also can adjust the mechanical properties of the hydrogel as needed after injection to achieve a long-term residence of the hydrogel in situ, thereby improving the therapeutic effect of cell transplantation.

[0008] The present invention provides a three-component double-reaction hydrogel material, which is formed by cross-linking a first component, a second component and a third component;

[0009] The first component includes a polymer containing benzaldehyde functional groups;

[0010] The second component includes a polymer containing cyanoalkyl ester functional groups;

[0011] The third component includes a compound containing a thiol group and a carboxyl group.

[0012] Preferably, the polymer containing benzaldehyde functional groups is selected from benzaldehyde functionalized polysaccharide polymers and / or benzaldehyde functionalized multi-arm polyethylene glycol;

[0013] The polymer containing cyanoalkyl ester functional groups is selected from cyanoalkyl ester functionalized polysaccharide polymers and / or cyanoalkyl ester functionalized multi-arm polyethylene glycol;

[0014] The compound containing thiol and carboxyl groups is shown in formula A:

[0015] Formula A

[0016] Wherein, x is an integer of 0 to 5; and R is H, a C1 to C5 amide group or a C1 to C5 alkyl group.

[0017] Preferably, the polymer containing benzaldehyde functional groups is selected from one or more of benzaldehyde functionalized hyaluronic acid, benzaldehyde functionalized sodium hyaluronate, benzaldehyde functionalized dextran, benzaldehyde functionalized three-arm polyethylene glycol, benzaldehyde functionalized four-arm polyethylene glycol, benzaldehyde functionalized six-arm polyethylene glycol and benzaldehyde functionalized eight-arm polyethylene glycol;

[0018] The polymer containing cyanoalkyl ester functional groups is selected from one or more of cyanoalkyl ester functionalized hyaluronic acid, cyanoalkyl ester functionalized sodium hyaluronate, cyanoalkyl ester functionalized dextran, cyanoalkyl ester functionalized three-arm polyethylene glycol, cyanoalkyl ester functionalized four-arm polyethylene glycol, cyanoalkyl ester functionalized six-arm polyethylene glycol and cyanoalkyl ester functionalized eight-arm polyethylene glycol;

[0019] The polymer containing cyanoalkyl ester functional groups is a polymer containing cyanoacetate functional groups.

[0020] Preferably, the first component comprises one or more structures represented by formula (I-1) to formula (I-4):

[0021]

[0022]

[0023]

[0024]

[0025] wherein m, n, o, p, d, and z are the numbers of repeating units, m and n are each independently an integer of 10 to 100, and o, p, d, and z are each independently an integer of 20 to 300.

[0026] Preferably, the second component comprises one or more structures represented by formula (II-1) to formula (II-4):

[0027]

[0028]

[0029]

[0030]

[0031] wherein z, g, e, q, j and h are the number of repeating units, z and g are each independently an integer of 10 to 100, and e, q, j and h are each independently an integer of 20 to 300.

[0032] Preferably, the third component includes one or more structures represented by formula (III-1) to formula (III-3):

[0033] .

[0034] Preferably, the mass ratio of the first component to the second component is 1:(0.1-10);

[0035] The mass ratio of the third component to the first component or the second component is 1:(3~320).

[0036] The present invention also provides a method for preparing the above-mentioned three-component double-reaction hydrogel material, comprising the following steps:

[0037] S1) providing a solution of a first component;

[0038] providing a solution of a second component;

[0039] providing a solution of a third component;

[0040] S2) mixing the solution of the first component with the solution of the second component to perform a cross-linking reaction to obtain a primary hydrogel;

[0041] S3) adding a solution of a third component to the primary hydrogel to obtain a three-component double-reaction hydrogel material.

[0042] Preferably, the concentration of the first component in the solution of the first component is 20-200 mg / mL;

[0043] The concentration of the second component in the solution of the second component is 20-200 mg / mL;

[0044] The concentration of the third component in the solution of the third component is 1.64-16.4 mg / mL;

[0045] The solvents of the solution of the first component, the solution of the second component and the solution of the third component are independently selected from one or more of water, physiological saline and buffer solution.

[0046] The present invention also provides an application of the above three-component double-reaction hydrogel material as a cell transplantation therapy carrier.

[0047] The present invention provides a three-component double-reaction hydrogel material, which is formed by cross-linking a first component, a second component and a third component; the first component includes a polymer containing a benzaldehyde functional group; the second component includes a polymer containing a cyanoalkyl ester functional group; and the third component includes a compound containing a thiol group and a carboxyl group. Compared with the prior art, the three-component double-reaction hydrogel provided by the present invention is a hydrogel material cross-linked by a dynamic chemical bond constructed by a C=C double bond formed by a Knoevenagel condensation reaction and pH responsiveness induced by thiol and carboxyl compounds and Michael addition reaction. The preparation conditions are mild, the gelation speed is fast, and the mechanical properties of the hydrogel can be adjusted in situ as needed after injection to achieve a long-term retention of the hydrogel, thereby improving the therapeutic effect of cell transplantation, so that the three-component double-reaction hydrogel with rapid gelation and the ability to adjust the mechanical properties of the hydrogel in situ as needed can be used as a cell transplantation treatment carrier in the field of biomedical materials. Compared with traditional transplant carriers, the three-component dual-reaction hydrogel in the present invention can be used as a cell transplant carrier to improve the survival rate of cells during the injection process, and can achieve long-term residence in situ through in situ regulation, ensuring that cells can grow rapidly in the hydrogel carrier and improving the therapeutic effect of cell transplantation.

[0048] The experimental results show that the three-component dual-reaction hydrogel of the present invention has a faster gelation speed, and the hydrogel has a relatively regular porous grid structure inside. At the same time, due to the dynamic nature of the cross-linking points, the primary hydrogel has good self-healing and shear-thinning properties, and can protect the encapsulated cells from shear damage during injection, thereby improving cell survival rate. The three-component dual-reaction hydrogel can achieve on-demand regulation of mechanical strength and stability by adjusting the ratio of thiol and carboxyl compounds. Cytotoxicity experiments show that the hydrogel has no obvious cytotoxicity, and can therefore be used as an injectable hydrogel material with on-demand adjustable mechanical properties as a carrier material for cell transplantation therapy. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of the 4-arm PEG-CA prepared in Example 1 of the present invention;

[0050] Figure 2 This is the hydrogen nuclear magnetic resonance spectrum of 4-arm PEG-FA prepared in Example 5 of the present invention;

[0051] Figure 3 is the gelation time of the mixed solution prepared in Example 9 of the present invention at 25°C;

[0052] Figure 4Graphs showing changes in the storage modulus of the hydrogels prepared in Example 19, Example 20 and Example 21 of the present invention over time during the gelation process; wherein A is a graph showing changes in the storage modulus of the hydrogel prepared in Example 19 over time during the gelation process, B is a graph showing changes in the storage modulus of the hydrogel prepared in Example 20 over time during the gelation process, and C is a graph showing changes in the storage modulus of the hydrogel prepared in Example 21 over time during the gelation process;

[0053] Figure 5 This is a graph showing the self-healing performance of the hydrogel prepared in Example 22 of the present invention;

[0054] Figure 6 This is a shear thinning performance curve of the hydrogel prepared in Example 23 of the present invention;

[0055] Figure 7 This is a scanning electron microscope (SEM) image of the primary hydrogel prepared in Example 25 of the present invention;

[0056] Figure 8 This is a scanning electron microscope (SEM) image of the primary hydrogel prepared in Example 40 of the present invention;

[0057] Fig. 9 Graphs of storage modulus and loss modulus of the hydrogels prepared in Example 10, Example 31, Example 32, Example 33, and Example 34 of the present invention without and at different N-acetylcysteine ​​concentrations; wherein, A is a graph of storage modulus and loss modulus of the hydrogel prepared in Example 10 without and at different N-acetylcysteine ​​concentrations; B is a graph of storage modulus and loss modulus of the hydrogel prepared in Example 31 without and at different N-acetylcysteine ​​concentrations; C is a graph of storage modulus and loss modulus of the hydrogel prepared in Example 32 without and at different N-acetylcysteine ​​concentrations; D is a graph of storage modulus and loss modulus of the hydrogel prepared in Example 33 without and at different N-acetylcysteine ​​concentrations; E is a graph of storage modulus and loss modulus of the hydrogel prepared in Example 34 without and at different N-acetylcysteine ​​concentrations;

[0058] Fig.10 The degradation curves of the hydrogels prepared in Examples 10 and 34 of the present invention at different N-acetylcysteine ​​concentrations;

[0059] Fig.11 The present invention provides a graph showing the cytotoxicity of the three-component dual-reaction hydrogel material at different concentrations to L929 cells;

[0060] Fig.12 The invention provides a graph of the proliferation of L929 cells in a three-component dual-reaction hydrogel material of different concentrations;

[0061] Fig.13 This is a characterization diagram of the protective effect of the three-component dual-reaction hydrogel of the present invention on encapsulated cells during the injection process. DETAILED DESCRIPTION

[0062] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0063] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0064] There is no particular limitation on the purity of all raw materials in the present invention. The present invention preferably uses analytically pure materials or materials that meet the purity standards related to the preparation of cell transplantation vectors.

[0065] The sources and abbreviations of all raw materials in the present invention are conventional sources and abbreviations in the field, and are clear and definite in the field of their relevant uses. Those skilled in the art can purchase them from commercial sources or prepare them by conventional methods based on the abbreviations and corresponding uses.

[0066] In particular, the present invention involves many new structures or substituent groups. Therefore, the present invention names the above structures and groups in accordance with the naming principles well known in the art, and those skilled in the art can clearly and clearly know the meaning of the present invention based on the common sense in the art. Among them, due to the difference in naming principles, the names of some structures and substituent groups may not be unique. In the present invention, references can also be made based on reaction mechanisms, reaction routes and specific structural formulas.

[0067] The invention provides a three-component double-reaction hydrogel material, which is formed by cross-linking a first component, a second component and a third component; the first component comprises a polymer containing a benzaldehyde functional group; the second component comprises a polymer containing a cyanoalkyl ester functional group; and the third component comprises a compound containing a thiol group and a carboxyl group.

[0068] The three-component double-reaction hydrogel material provided by the present invention is prepared from three components, namely, a polymer containing a benzaldehyde functional group, a polymer containing a cyanoalkyl ester functional group, and a compound containing a thiol group and a carboxyl group, through a Knoevenagel condensation reaction and a Michael addition reaction. The three-component double-reaction hydrogel material has the properties of shear thinning and self-healing, can protect the encapsulated cells during the injection process, and can adjust the mechanical properties of the hydrogel as needed after the injection to achieve a long-term retention of the hydrogel in situ, and can be used as a cell transplantation carrier.

[0069] According to the present invention, the polymer containing benzaldehyde functional groups is preferably a benzaldehyde-functionalized polysaccharide polymer and / or a benzaldehyde-functionalized multi-arm polyethylene glycol, more preferably one or more of benzaldehyde-functionalized hyaluronic acid, benzaldehyde-functionalized sodium hyaluronate, benzaldehyde-functionalized dextran, benzaldehyde-functionalized three-arm polyethylene glycol, benzaldehyde-functionalized four-arm polyethylene glycol, benzaldehyde-functionalized six-arm polyethylene glycol and benzaldehyde-functionalized eight-arm polyethylene glycol.

[0070] In a specific embodiment provided by the present invention, the first component includes one or more structures represented by formula (I-1) to formula (I-4):

[0071]

[0072]

[0073]

[0074]

[0075] Among them, m, n, o, p, d, and z in formula (I~4) are the number of repeating units, and m and n are each independently preferably an integer of 10 to 100, more preferably an integer of 20 to 100, further preferably an integer of 40 to 80, and most preferably an integer of 40 to 60; o, p, d, and z in formula (I~4) are each independently preferably an integer of 20 to 300, more preferably an integer of 50 to 250, further preferably an integer of 50 to 200, further preferably an integer of 70 to 150, and most preferably an integer of 100 to 120.

[0076] According to the present invention, the polymer containing cyanoalkyl ester functional groups is preferably a cyanoalkyl ester functionalized polysaccharide polymer and / or a cyanoalkyl ester functionalized multi-arm polyethylene glycol, more preferably one or more of cyanoalkyl ester functionalized hyaluronic acid, cyanoalkyl ester functionalized sodium hyaluronate, cyanoalkyl ester functionalized dextran, cyanoalkyl ester functionalized three-arm polyethylene glycol, cyanoalkyl ester functionalized four-arm polyethylene glycol, cyanoalkyl ester functionalized six-arm polyethylene glycol and cyanoalkyl ester functionalized eight-arm polyethylene glycol.

[0077] According to the present invention, the polymer containing cyanoalkyl ester functional groups is preferably a polymer containing cyanoacetate functional groups.

[0078] In a specific embodiment provided by the present invention, the second component includes one or more structures represented by formula (II-1) to formula (II-4):

[0079]

[0080]

[0081]

[0082]

[0083] Among them, z, g, e, q, j and h in formula (II-1) are the number of repeating units, and z and g in formula (II-1) are each independently preferably an integer of 10 to 100, more preferably an integer of 20 to 100, further preferably an integer of 40 to 80, and most preferably an integer of 40 to 60; e, q, j and h are each independently preferably an integer of 20 to 300, more preferably an integer of 50 to 250, further preferably an integer of 50 to 200, further preferably an integer of 70 to 150, and most preferably an integer of 100 to 120.

[0084] According to the present invention, the compound containing thiol and carboxyl groups is preferably as shown in Formula A:

[0085] Formula A

[0086] Among them, x is preferably an integer of 0 to 5, more preferably an integer of 0 to 3, and more preferably 0, 1 or 2; R is preferably H, C2 to C5 amide or C1 to C5 alkyl, more preferably H, C2 to C4 amide or C1 to C4 alkyl, and more preferably H, C2 to C3 amide or C1 to C3 alkyl.

[0087] In a specific embodiment provided by the present invention, the third component includes one or more structures represented by formula (III-1) to formula (III-3):

[0088] .

[0089] According to the present invention, the mass ratio of the first component to the second component is preferably 1:(0.1-10), more preferably 1:(0.2-5), further preferably 1:(0.5-2), and most preferably 1:1.

[0090] According to the present invention, the mass ratio of the third component to the first component or the second component is preferably 1: (3-320), more preferably 1: (3-160), more preferably 1: (10-100), more preferably 1: (15-80), more preferably 1: (25-50), and most preferably 1: (35-45); in some embodiments provided by the present invention, the mass ratio of the third component to the first component or the second component is specifically 1: 152.4, 1: 30, 1: 15.2, 1: 305, 1: 150, 1: 61, 1: 30.5, 1: 47 or 1: 54.

[0091] According to the present invention, the first component, the second component and the third component are preferably formed by cross-linking in an aqueous medium; the aqueous medium is preferably an aqueous solvent, more preferably one or more of water, physiological saline and buffer solution.

[0092] According to the present invention, the polymer containing benzaldehyde functional groups of the first component and the polymer containing cyanoacetate functional groups of the second component undergo Knoevenagel condensation reaction, preferably forming a dynamic covalent cross-linked structure of C=C bonds; the compound containing thiol and carboxyl groups of the third component combines with the C=C bond through a Michael addition reaction to obtain a three-component dual-reaction hydrogel material with adjustable mechanical properties.

[0093] According to the present invention, the three-component dual-reaction hydrogel material is a three-component dual-reaction hydrogel whose mechanical properties and stability can be regulated as required.

[0094] According to the present invention, the three-component double-reaction hydrogel is formed by cross-linking the primary hydrogel and the third component; the primary hydrogel is formed by cross-linking the first component and the second component; the primary hydrogel is preferably an injectable hydrogel, which can be injected; the injectable use in the present invention means that it can be injected after gelation. More specifically, the primary hydrogel has a self-repairing function.

[0095] According to the present invention, the three-component dual-reaction hydrogel has an adjustable storage modulus.

[0096] According to the present invention, the three-component dual-reaction hydrogel has adjustable stability.

[0097] The three-component double-reaction hydrogel provided by the present invention is a hydrogel material cross-linked by dynamic chemical bonds constructed by a Knoevenagel condensation reaction and pH responsiveness induced by sulfhydryl and carboxyl compounds and Michael addition reaction. The preparation conditions are mild, the gelation speed is fast, and the mechanical properties of the hydrogel can be adjusted in situ as needed after injection to achieve long-term retention of the hydrogel, thereby improving the therapeutic effect of cell transplantation. Thus, the three-component double-reaction hydrogel with rapid gelation and the ability to adjust the mechanical properties of the hydrogel in situ as needed can be used as a cell transplantation treatment carrier in the field of biomedical materials. Compared with traditional transplantation carriers, the three-component double-reaction hydrogel in the present invention can be used as a cell transplantation carrier to improve the survival rate of cells during the injection process, and can achieve long-term retention in situ through in situ regulation, ensuring that cells can grow rapidly in the hydrogel carrier and improving the therapeutic effect of cell transplantation.

[0098] The present invention also provides a method for preparing the above-mentioned three-component dual-reaction hydrogel material, comprising the following steps: S1) providing a solution of a first component; providing a solution of a second component; providing a solution of a third component; S2) mixing the solution of the first component with the solution of the second component for a cross-linking reaction to obtain a primary hydrogel; S3) adding the solution of the third component to the primary hydrogel to obtain a three-component dual-reaction hydrogel material.

[0099] The present invention has no special restrictions on the sources of all raw materials, and any raw materials available on the market can be used. The first component, the second component and the third component are the same as those described above, and will not be described in detail here.

[0100] In a specific embodiment provided by the present invention, the polymer containing benzaldehyde functional groups is prepared according to the following method: a polymer containing hydroxyl groups, alkanoylbenzoic acid, an acylation catalyst and a condensation agent are reacted in a solvent to obtain a polymer containing benzaldehyde functional groups; the polymer containing hydroxyl groups is preferably a polysaccharide polymer and / or a multi-arm polyethylene glycol, more preferably one or more of hyaluronic acid, sodium hyaluronate, dextran, three-arm polyethylene glycol, four-arm polyethylene glycol, six-arm polyethylene glycol and eight-arm polyethylene glycol; the alkanoylbenzoic acid is preferably p-formylbenzoic acid; the acylation catalyst is preferably dimethylaminopyridine (DMAP); the condensation agent is preferably a carbodiimide series condensation agent, such as N, N'-dicyclohexylcarbodiimide (DCC), N, N'-diisopropylcarbodiimide (DIC) and 1-ethyl-(3 -dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl); the mass ratio of the acylation catalyst to the condensation agent is preferably (0.06~0.15): (2~3.8); the mass ratio of the polymer containing a hydroxyl group to the acylation catalyst is preferably 5: (0.06~0.15); the solvent is preferably one or more of dichloromethane, dimethyl sulfoxide and water; the mass ratio of the polymer containing a hydroxyl group to the alkanoylbenzoic acid is preferably 5: (1~5), more preferably 5: (1.5~5); the reaction temperature is preferably 20°C~30°C, more preferably 25°C; when the polymer containing a hydroxyl group is a multi-arm polyethylene glycol, the reaction time is preferably 30~60 h, more preferably 35~55 h, more preferably 40~55 h, more preferably 45~50 h, and most preferably 48 h; after the reaction is completed, preferably washing with cold saturated sodium chloride solution and cold saturated sodium bicarbonate solution in sequence, collecting the organic phase, concentrating it and precipitating it with cold ether to obtain a solid initial product, and then dialyzing the solid initial product in deionized water for purification and freeze-drying it to obtain a polymer containing benzaldehyde functional groups; the dialysis time is preferably 60-80 h, more preferably 70-75 h, and more preferably 72 h; or when the polymer containing hydroxyl groups is a polysaccharide polymer, the reaction time is preferably 1-3 days, more preferably 2 days; after the reaction is completed, the reactant is dialyzed in deionized water and freeze-dried to obtain a polymer containing benzaldehyde functional groups; the dialysis time is preferably 60-80 h, more preferably 70-75 h, and more preferably 72 h.

[0101] In a specific embodiment provided by the present invention, the polymer containing cyanoalkyl ester functional groups is prepared according to the following method: a polymer containing a hydroxyl group, a cyanoalkyl acid, an acylation catalyst and a condensation agent are reacted in a solvent to obtain a polymer containing a cyanoalkyl ester functional group; the polymer containing a hydroxyl group is preferably a polysaccharide polymer and / or a multi-arm polyethylene glycol, more preferably one or more of hyaluronic acid, sodium hyaluronate, dextran, a three-arm polyethylene glycol, a four-arm polyethylene glycol, a six-arm polyethylene glycol and an eight-arm polyethylene glycol; the number of carbon atoms of the alkyl group in the cyanoalkyl acid is preferably 1 to 5, more preferably 1 to 4, and more preferably 2 to 3; the acylation catalyst is preferably dimethylaminopyridine (DMAP); the condensation agent is preferably a carbodiimide series condensation agent, such as N, N'-dicyclohexylcarbodiimide (DCC), N, N'-diisopropylcarbodiimide (DIC) and 1-ethyl-(3 -dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl); the mass ratio of the acylation catalyst to the condensation agent is preferably (0.06~0.15): (2~3.8); the mass ratio of the polymer containing a hydroxyl group to the acylation catalyst is preferably 5: (0.06~0.15); the solvent is preferably one or more of dichloromethane, dimethyl sulfoxide and water; the mass ratio of the polymer containing a hydroxyl group to the cyanoalkyl acid is preferably 5: (1~3); the reaction temperature is preferably 20°C~30°C, more preferably 25°C; when the polymer containing a hydroxyl group is a multi-arm polyethylene glycol, the reaction time is preferably 30~60 h, more preferably 35~55 h, more preferably 40~55 h, more preferably 45~50 h, and most preferably 48 h; after the reaction is completed, preferably washing with cold saturated sodium chloride solution and cold saturated sodium bicarbonate solution in sequence, collecting the organic phase, concentrating it and precipitating it with cold ether to obtain a solid initial product, and then dialyzing the solid initial product in deionized water for purification and freeze-drying it to obtain a polymer containing cyanoalkyl ester functional groups; the dialysis time is preferably 60-80 h, more preferably 70-75 h, and more preferably 72 h; or when the polymer containing hydroxyl groups is a polysaccharide polymer, the reaction time is preferably 1-3 days, more preferably 2 days; after the reaction is completed, the reactant is dialyzed in deionized water and freeze-dried to obtain a polymer containing cyanoalkyl ester functional groups; the dialysis time is preferably 60-80 h, more preferably 70-75 h, and more preferably 72 h.

[0102] According to the present invention, the concentration of the first component in the solution of the first component is preferably 20-200 mg / mL, more preferably 50-150 mg / mL, further preferably 70-120 mg / mL, and most preferably 80-100 mg / mL; the solvent of the solution of the first component is preferably one or more of water, physiological saline and buffer solution; the buffer solution is preferably PBS buffer.

[0103] According to the present invention, the solution of the first component is prepared according to the following method: a polymer containing a benzaldehyde functional group is mixed with an aqueous solvent to obtain a solution of the first component; the aqueous solvent can be an aqueous solvent well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably one or more of water, physiological saline and buffer solution; the mixing temperature is preferably 4°C to 37°C, more preferably 6°C to 35°C, more preferably 8°C to 32°C, more preferably 12°C to 28°C, more preferably 16°C to 24°C, and more preferably 19°C to 21°C.

[0104] According to the present invention, the concentration of the second component in the solution of the second component is preferably 20-200 mg / mL, more preferably 50-150 mg / mL, further preferably 70-120 mg / mL, and most preferably 80-100 mg / mL; the solvent of the solution of the second component is preferably one or more of water, physiological saline and buffer solution; the buffer solution is preferably PBS buffer.

[0105] According to the present invention, the solution of the second component is prepared according to the following method: a polymer containing a cyanoalkyl ester functional group is mixed with an aqueous solvent to obtain a solution of the second component; the aqueous solvent can be an aqueous solvent well known to those skilled in the art, and there is no special limitation. In the present invention, it is preferably one or more of water, physiological saline and buffer solution; the mixing temperature is preferably 4°C to 37°C, more preferably 6°C to 35°C, more preferably 8°C to 32°C, more preferably 12°C to 28°C, more preferably 16°C to 24°C, and more preferably 19°C to 21°C.

[0106] The concentration of the third component in the solution of the third component is 1.64~16.4 mg / mL, more preferably 3~14 mg / mL, more preferably 5~12 mg / mL, and most preferably 8~10 mg / mL; the solvent of the solution of the third component is preferably one or more of water, saline and buffer solution; the buffer solution is preferably PBS buffer.

[0107] According to the present invention, the solution of the third component is prepared according to the following method: a compound containing a thiol group and a carboxyl group is mixed with an aqueous solvent to obtain a solution of the third component; the aqueous solvent can be an aqueous solvent well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably one or more of water, physiological saline and buffer solution; the mixing temperature is preferably 4°C to 37°C, more preferably 6°C to 35°C, more preferably 8°C to 32°C, more preferably 12°C to 28°C, more preferably 16°C to 24°C, and more preferably 19°C to 21°C.

[0108] The solution of the first component and the solution of the second component are mixed for cross-linking reaction to obtain a primary hydrogel; the mass ratio of the first component in the solution of the first component to the second component in the solution of the second component is preferably 1: (0.1-10), more preferably 1: (0.2-5), more preferably 1: (0.5-2), and most preferably 1: 1; the mixing temperature is preferably 4°C-37°C, more preferably 6°C-35°C, more preferably 8°C-32°C, more preferably 12°C-28°C, more preferably 16°C-24°C, and more preferably 19°C-21°C; the cross-linking reaction temperature is preferably 4°C-37°C, more preferably 6°C-35°C, more preferably 8°C-32°C, more preferably 12°C-28°C, more preferably 16°C-24°C, and more preferably 19°C-21°C; the cross-linking reaction time is preferably 3-100 min, more preferably 5-60 min, more preferably 10-40 min, and most preferably 15-30 min.

[0109] A solution of the third component is added to the primary hydrogel to obtain a three-component double-reaction hydrogel material; the solution of the third component is preferably added dropwise to the primary hydrogel for blending; the blending temperature is preferably 4°C to 37°C, more preferably 6°C to 35°C, more preferably 8°C to 32°C, more preferably 12°C to 28°C, more preferably 16°C to 24°C, and more preferably 19°C to 21°C.

[0110] The present invention also provides an application of the above three-component double-reaction hydrogel material as a cell transplantation therapy carrier.

[0111] More specifically, the present invention first mixes the cells to be transplanted with the first component and the second component to form a primary hydrogel encapsulating the cells; and then adds the third component to the primary hydrogel encapsulating the cells for cross-linking after injection.

[0112] The present invention dissolves a polymer containing a benzaldehyde functional group, a polymer containing a cyanoalkyl ester functional group, and a compound containing a thiol group and a carboxyl group in an aqueous solvent to obtain a uniform solution; the obtained benzaldehyde polymer solution is first uniformly mixed with a polymer solution containing a cyanoacetate functional group, and a cross-linking reaction is performed to obtain a primary hydrogel material; a compound solution containing a thiol group and a carboxyl group is added to the obtained hydrogel material to obtain a three-component double-reaction hydrogel material. The hydrogel material has properties such as injectability and mechanical strength and stability that can be adjusted as needed. The three-component double-reaction hydrogel provided by the present invention is a three-component double-reaction hydrogel material based on a dynamic C=C double bond formed by a Knoevenagel condensation reaction, pH responsiveness induced by carboxyl groups and thiol groups, and dynamic chemical bond cross-linking constructed by Michael addition reaction, and the preparation conditions are mild, the gelation speed is fast, and the mechanical properties of the hydrogel can be adjusted in situ as needed after injection. This three-component double-reaction hydrogel can be used as a cell transplantation treatment carrier to achieve a high survival rate of encapsulated cells and a long-term retention of the hydrogel during the injection process, thereby improving the therapeutic effect of cell transplantation at one time.

[0113] In order to further illustrate the present invention, a three-component dual-reaction hydrogel material, a preparation method and application thereof provided by the present invention are described in detail below in conjunction with embodiments.

[0114] The reagents used in the following examples are all commercially available; the number average molecular weight of the four-arm polyethylene glycol used in the examples is 10,000 g / mol; the number average molecular weight of the eight-arm polyethylene glycol is 20,000 g / mol; the number average molecular weight of dextran is 70,000 g / mol; and the number average molecular weight of hyaluronic acid is 100,000 g / mol.

[0115] Example 1

[0116] 5 g of four-arm polyethylene glycol (4-arm PEG), 0.06 g of dimethylaminopyridine (DMAP) and 1.5 g of 4-formylbenzoic acid were dissolved in 100 mL of anhydrous dichloromethane, and then 2 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride was added to the reaction solution. The reaction was carried out at 25°C for 48 h, and the reaction solution was washed 3 times with a cold saturated sodium chloride solution, 50 mL each time. Then, the reaction solution was washed 3 times with a cold saturated sodium bicarbonate solution, 50 mL each time. After washing, the lower organic phase was collected, an appropriate amount of anhydrous magnesium sulfate was added thereto, dried for 12 h, and then filtered to obtain a filtrate. The filtrate was concentrated by rotary evaporation and precipitated in cold ether for several times, and the solid initial product was filtered to obtain a solid product. Then, it was dialyzed in deionized water for 72 h and freeze-dried to obtain a powdered product (4-arm PEG-FA) containing a benzaldehyde functional group having the structure shown in Formula I-1.

[0117] The 4-arm PEG-FA obtained above was subjected to nuclear magnetic resonance analysis. Figure 1 , Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of the 4-arm PEG-FA prepared in Example 1 of the present invention.

[0118] Example 2

[0119] 5 g of eight-arm polyethylene glycol (8-arm PEG), 0.06 g of dimethylaminopyridine (DMAP) and 1.5 g of 4-formylbenzoic acid were dissolved in 100 mL of anhydrous dichloromethane, and then 2 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC•HCl) was added to the reaction solution. The reaction was carried out at 25°C for 48 h, and the reaction solution was washed with cold saturated sodium chloride solution 3 times, 50 mL each time. Then, it was washed with cold saturated sodium bicarbonate solution 3 times, 50 mL each time. After washing, the lower organic phase was collected, an appropriate amount of anhydrous magnesium sulfate was added thereto, dried for 12 h, and then filtered to obtain a filtrate. The filtrate was concentrated by rotary evaporation and precipitated in cold ether for several times, and the solid initial product was filtered to obtain a solid product. It was then dialyzed in deionized water for 72 h and freeze-dried to obtain a powdered product (8-arm PEG-FA) containing a benzaldehyde functional group having the structure shown in Formula I-2.

[0120] Example 3

[0121] 5 g of dextran, 0.15 g of DMAP and 5 g of 4-formylbenzoic acid were dissolved in 150 mL of anhydrous DMSO solution, respectively. Then 3.8 g of EDC•HCl was added to the reaction system. After reacting at 25°C for two days, the reaction mixture was dialyzed in deionized water for 72 h and freeze-dried to obtain a white product having a polymer sample (Dex-FA) containing benzaldehyde functional groups with the structure shown in Formula I-3.

[0122] Example 4

[0123] 5 g hyaluronic acid, 0.15 g DMAP and 5 g 4-formylbenzoic acid were dissolved in 150 mL anhydrous DMSO solution respectively, and then 3.8 g EDC•HCl was added to the reaction system. After reacting at 25°C for two days, the reaction mixture was dialyzed in deionized water for 72 h and freeze-dried to obtain a white product having a polymer sample (HA-FA) containing benzaldehyde functional groups with the structure shown in Formula I-4.

[0124] Example 5

[0125] 5 g of four-arm polyethylene glycol (4-arm PEG), 0.06 g of dimethylaminopyridine (DMAP) and 1 g of cyanoacetic acid were dissolved in 100 mL of anhydrous dichloromethane, and then 2 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride was added to the reaction solution. The reaction was carried out at 25°C for 48 h, and the reaction solution was washed 3 times with a cold saturated sodium chloride solution, 50 mL each time. Then, the reaction solution was washed 3 times with a cold saturated sodium bicarbonate solution, 50 mL each time. After washing, the lower organic phase was collected, an appropriate amount of anhydrous magnesium sulfate was added thereto and dried for 12 h, and then filtered to obtain a filtrate. The filtrate was concentrated by rotary evaporation and precipitated in cold ether several times, and the solid initial product was filtered to obtain a solid product. It was then dialyzed in deionized water for 72 h and freeze-dried to obtain a powdered product (4-arm PEG-CA) containing a cyanoacetate functional group having the structure shown in Formula II-1.

[0126] The 4-arm PEG-CA obtained above was subjected to nuclear magnetic resonance analysis. Figure 2 , Figure 2 This is the hydrogen nuclear magnetic resonance spectrum of 4-arm PEG-FA prepared in Example 5 of the present invention.

[0127] Example 6

[0128] 5 g of eight-arm polyethylene glycol (8-arm PEG), 0.06 g of dimethylaminopyridine (DMAP) and 1 g of cyanoacetic acid were dissolved in 100 mL of anhydrous dichloromethane, and then 2 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride was added to the reaction solution. The reaction was carried out at 25 °C for 48 h, and the reaction solution was washed 3 times with a cold saturated sodium chloride solution, 50 mL each time. Then, the reaction solution was washed 3 times with a cold saturated sodium bicarbonate solution, 50 mL each time. After washing, the lower organic phase was collected, an appropriate amount of anhydrous magnesium sulfate was added thereto and dried for 12 h, and then filtered to obtain a filtrate. The filtrate was concentrated by rotary evaporation and precipitated in cold ether several times, and the solid initial product was filtered to obtain a solid product. It was then dialyzed in deionized water for 72 h and freeze-dried to obtain a powdered product (8-arm PEG-CA) containing a cyanoacetate functional group having the structure shown in formula II-2.

[0129] Example 7

[0130] 5 g of dextran, 0.15 g of DMAP and 3 g of cyanoacetic acid were dissolved in 150 mL of anhydrous DMSO solution, and then 3.8 g of EDC•HCl was added to the reaction system. After two days of reaction at 25°C, the reaction mixture was dialyzed in deionized water for 72 h and freeze-dried to obtain a light yellow product having a polymer sample (Dex-CA) containing cyanoacetate functional groups and having the structure shown in Formula II-3.

[0131] Example 8

[0132] 5 g hyaluronic acid, 0.15 g DMAP and 3 g cyanoacetic acid were dissolved in 150 mL anhydrous DMSO solution, and then 3.8 g EDC•HCl was added to the reaction system. After two days of reaction at 25°C, the reaction mixture was dialyzed in deionized water for 72 h and freeze-dried to obtain a light yellow product having a polymer sample (HA-CA) containing cyanoacetate functional groups with the structure shown in formula II-4.

[0133] Example 9

[0134] The 4-arm PEG-FA (50 mg) prepared in Example 1 was dissolved in PBS solution (1 mL) to obtain solution 1; the 4-arm PEG-CA (50 mg) prepared in Example 5 was dissolved in PBS solution (1 mL) to obtain solution 2; solution 1 (150 μL) and solution 2 (150 μL) were fully stirred to obtain a mixed solution, and the mixed solution was transferred to a rheometer to characterize its gelation time at 25°C.

[0135] See also Figure 3 , Figure 3 is the gelation time of the mixed solution prepared in Example 9 of the present invention at 25°C. Figure 3 As shown, the intersection of G' and G'' is around 20 min, proving that the gelation time is 20 min and the primary hydrogel is obtained.

[0136] Example 10

[0137] The 4-arm PEG-FA (100 mg) prepared in Example 1 was dissolved in PBS solution (1 mL) to obtain solution 3; the 4-arm PEG-CA (100 mg) prepared in Example 5 was dissolved in PBS solution (1 mL) to obtain solution 4; solution 3 (150 μL) and solution 4 (150 μL) were fully stirred to obtain a mixed solution, and the mixed solution was transferred to a rheometer to characterize its gelation time at 25°C. The gelation time was 15 min, and a primary hydrogel was obtained.

[0138] Embodiment 11

[0139] The 4-arm PEG-FA (150 mg) prepared in Example 1 was dissolved in PBS solution (1 mL) to obtain solution 5; the 4-arm PEG-CA (150 mg) prepared in Example 5 was dissolved in PBS solution (1 mL) to obtain solution 6; solution 5 (150 μL) and solution 6 (150 μL) were fully stirred to obtain a mixed solution, and the mixed solution was transferred to a rheometer to characterize its gelation time at 25°C. The gelation time was 10 min, and a primary hydrogel was obtained.

[0140] Example 12

[0141] The 8-arm PEG-FA (50 mg) prepared in Example 2 was dissolved in PBS solution (1 mL) to obtain solution 7; the 8-arm PEG-CA (50 mg) prepared in Example 6 was dissolved in PBS solution (1 mL) to obtain solution 8; solution 7 (150 μL) and solution 8 (150 μL) were fully stirred to obtain a mixed solution, and the mixed solution was transferred to a rheometer to characterize its gelation time at 25°C. The gelation time was 10 min, and a primary hydrogel was obtained.

[0142] Example 13

[0143] The 8-arm PEG-FA (100 mg) prepared in Example 2 was dissolved in PBS solution (1 mL) to obtain solution 9; the 8-arm PEG-CA (100 mg) prepared in Example 6 was dissolved in PBS solution (1 mL) to obtain solution 10; solution 9 (150 μL) and solution 10 (150 μL) were fully stirred to obtain a mixed solution, and the mixed solution was transferred to a rheometer to characterize its gelation time at 25°C. The gelation time was 5 min, and a primary hydrogel was obtained.

[0144] Embodiment 14

[0145] The 8-arm PEG-FA (150 mg) prepared in Example 2 was dissolved in PBS solution (1 mL) to obtain solution 11; the 8-arm PEG-CA (150 mg) prepared in Example 6 was dissolved in PBS solution (1 mL) to obtain solution 12; solution 11 (150 μL) and solution 12 (150 μL) were fully stirred to obtain a mixed solution, and the mixed solution was transferred to a rheometer to characterize its gelation time at 25°C. The gelation time was 2 min, and a primary hydrogel was obtained.

[0146] Embodiment 15

[0147] The Dex-FA (50 mg) prepared in Example 3 was dissolved in PBS solution (1 mL) to obtain solution 13; the Dex-CA (50 mg) prepared in Example 7 was dissolved in PBS solution (1 mL) to obtain solution 14; solution 13 (150 μL) and solution 14 (150 μL) were fully stirred to obtain a mixed solution, and the mixed solution was transferred to a rheometer to characterize its gelation time at 25°C. The gelation time was 15 min, and a primary hydrogel was obtained.

[0148] Example 16

[0149] The Dex-FA (100 mg) prepared in Example 3 was dissolved in PBS solution (1 mL) to obtain solution 15; the Dex-CA (100 mg) prepared in Example 7 was dissolved in PBS solution (1 mL) to obtain solution 16; solution 15 (150 μL) and solution 16 (150 μL) were fully stirred to obtain a mixed solution, and the mixed solution was transferred to a rheometer to characterize its gelation time at 25°C. The gelation time was 8 min, and a primary hydrogel was obtained.

[0150] Embodiment 17

[0151] The Dex-FA (150 mg) prepared in Example 3 was dissolved in PBS solution (1 mL) to obtain solution 17; the Dex-CA (150 mg) prepared in Example 7 was dissolved in PBS solution (1 mL) to obtain solution 18; solution 17 (150 μL) and solution 18 (150 μL) were fully stirred to obtain a mixed solution, and the mixed solution was transferred to a rheometer to characterize its gelation time at 25°C. The gelation time was 4 min, and a primary hydrogel was obtained.

[0152] Embodiment 18

[0153] The HA-FA (50 mg) prepared in Example 4 was dissolved in PBS solution (1 mL) to obtain solution 19; the HA-CA (50 mg) prepared in Example 8 was dissolved in PBS solution (1 mL) to obtain solution 20; solution 19 (150 μL) and solution 20 (150 μL) were fully stirred to obtain a mixed solution, and the mixed solution was transferred to a rheometer to characterize its gelation time at 25°C. The gelation time was 13 min, and a primary hydrogel was obtained.

[0154] Embodiment 19

[0155] The solution 1 (150 μL) and solution 2 (150 μL) obtained in Example 9 were fully stirred to obtain a mixed solution, which was transferred to a rotational rheometer to characterize the change of its storage modulus over time.

[0156] Embodiment 20

[0157] The solution 3 (150 μL) and solution 4 (150 μL) obtained in Example 10 were fully stirred to obtain a mixed solution, which was transferred to a rotational rheometer to characterize the change of its storage modulus over time.

[0158] Embodiment 21

[0159] The solution 5 (150 μL) and solution 6 (150 μL) obtained in Example 11 were fully stirred to obtain a mixed solution, which was transferred to a rotational rheometer to characterize the change of its storage modulus over time.

[0160] See also Figure 4 , Figure 4 1 is a graph showing the change of storage modulus over time during the gelation process of the hydrogels of Example 19 (5% by mass), Example 20 (10% by mass) and Example 21 (15% by mass) of the present invention; wherein A is a graph showing the change of storage modulus over time during the gelation process of the hydrogel prepared in Example 19, B is a graph showing the change of storage modulus over time during the gelation process of the hydrogel prepared in Example 20, and C is a graph showing the change of storage modulus over time during the gelation process of the hydrogel prepared in Example 21.

[0161] The results are as follows Figure 4 As shown, the storage modulus of the hydrogel increases rapidly. After complete cross-linking polymerization, the moduli of the hydrogel are 800 Pa, 2000 Pa, and 9000 Pa, respectively.

[0162] Embodiment 22

[0163] The solution 3 (150 μL) and solution 4 (150 μL) obtained in Example 10 were fully stirred to obtain a mixed solution, which was allowed to stand to obtain a primary hydrogel, which was transferred to a rotational rheometer to test its self-healing properties by alternating strain.

[0164] See also Figure 5 , Figure 5 This is a diagram of the self-healing performance of the primary hydrogel prepared in Example 22 of the present invention.

[0165] The results are as follows Figure 5 As shown in the figure, when the hydrogel is subjected to a 1500% strain, the storage modulus drops sharply and the hydrogel network is destroyed. When the strain is adjusted back to 1%, the storage modulus and loss modulus quickly return to their initial values. Figure 4 It can be seen that the primary hydrogel has good self-healing properties.

[0166] Embodiment 23

[0167] The solution 3 (150 μL) and solution 4 (150 μL) obtained in Example 10 were fully stirred to obtain a mixed solution, which was allowed to stand to obtain a primary hydrogel, which was transferred to a rotational rheometer, and the shear thinning properties of the primary hydrogel were tested by shear rate scanning.

[0168] See also Figure 6 , Figure 6 This is a shear thinning performance curve of the primary hydrogel prepared in Example 23 of the present invention. Figure 6 As shown, the viscosity of the hydrogel gradually decreases with the increase of shear rate, indicating that the hydrogel has good injectability.

[0169] Embodiment 24

[0170] Solution 5 (150 μL) and solution 6 (150 μL) obtained in Example 11 were fully stirred and allowed to stand to obtain a primary hydrogel, which was then transferred to a rotational rheometer. The shear thinning properties of the primary hydrogel were tested by shear rate sweep. The results showed that the viscosity of the hydrogel gradually decreased with increasing shear rate, indicating that the hydrogel had good injectability.

[0171] Embodiment 25

[0172] The primary hydrogel obtained in Example 10 was freeze-dried and then characterized by scanning electron microscopy (SEM).

[0173] See also Figure 7 , Figure 7 This is a scanning electron microscope (SEM) image of the primary hydrogel prepared in Example 25 of the present invention. Figure 7 As shown, the primary hydrogel has a porous structure.

[0174] Embodiment 26

[0175] The primary hydrogel obtained in Example 9 was freeze-dried and then characterized by scanning electron microscopy (SEM), which showed that the primary hydrogel had a porous structure.

[0176] Embodiment 27

[0177] The primary hydrogel prepared in Example 11 was freeze-dried and then characterized by scanning electron microscopy (SEM), which showed that the primary hydrogel had a porous structure.

[0178] Embodiment 28

[0179] The 4-arm PEG-FA (50 mg) prepared in Example 1 was dissolved in PBS solution (1 mL) to obtain solution 21; the 4-arm PEG-CA (50 mg) prepared in Example 5 was dissolved in PBS solution (1 mL) to obtain solution 22; N-acetylcysteine ​​(Mn: 164 g / mol, 1.64 mg) was dissolved in PBS (1 mL) to obtain solution 23; solution 21 (150 μL) and solution 22 (150 μL) were fully stirred to obtain a primary hydrogel, and solution 23 (30 μL) was added to the surface of the primary hydrogel obtained in this example, and the mixture was allowed to stand at room temperature to obtain a three-component double-reaction hydrogel.

[0180] Embodiment 29

[0181] The 4-arm PEG-FA (50 mg) prepared in Example 1 was dissolved in PBS solution (1 mL) to obtain solution 24; the 4-arm PEG-CA (50 mg) prepared in Example 5 was dissolved in PBS solution (1 mL) to obtain solution 25; N-acetylcysteine ​​(Mn: 164 g / mol, 8.2 mg) was dissolved in PBS (1 mL) to obtain solution 26; solution 24 (150 μL) and solution 25 (150 μL) were fully stirred to obtain a primary hydrogel, and solution 26 (30 μL) was added to the surface of the primary hydrogel obtained in this example, and the mixture was allowed to stand at room temperature to obtain a three-component double-reaction hydrogel.

[0182] Embodiment 30

[0183] The 4-arm PEG-FA (50 mg) prepared in Example 1 was dissolved in PBS solution (1 mL) to obtain solution 27; the 4-arm PEG-CA (50 mg) prepared in Example 5 was dissolved in PBS solution (1 mL) to obtain solution 28; N-acetylcysteine ​​(Mn: 164 g / mol, 16.4 mg) was dissolved in PBS (1 mL) to obtain solution 29; solution 27 (150 μL) and solution 28 (150 μL) were fully stirred to obtain a primary hydrogel, and solution 29 (30 μL) was added to the surface of the primary hydrogel obtained in this example, and the mixture was allowed to stand at room temperature to obtain a three-component double-reaction hydrogel.

[0184] Embodiment 31

[0185] The 4-arm PEG-FA (100 mg) prepared in Example 1 was dissolved in PBS solution (1 mL) to obtain solution 30; the 4-arm PEG-CA (100 mg) prepared in Example 5 was dissolved in PBS solution (1 mL) to obtain solution 31; N-acetylcysteine ​​(Mn: 164 g / mol, 1.64 mg) was dissolved in PBS (1 mL) to obtain solution 32; solution 30 (150 μL) and solution 31 (150 μL) were fully stirred to obtain a primary hydrogel; solution 32 (30 μL) was added to the surface of the primary hydrogel obtained in this example and allowed to stand at room temperature to obtain a three-component double-reaction hydrogel.

[0186] Embodiment 32

[0187] The 4-arm PEG-FA (100 mg) prepared in Example 1 was dissolved in PBS solution (1 mL) to obtain solution 33; the 4-arm PEG-CA (100 mg) prepared in Example 5 was dissolved in PBS solution (1 mL) to obtain solution 34; N-acetylcysteine ​​(Mn: 164 g / mol, 3.28 mg) was dissolved in PBS (1 mL) to obtain solution 35; solution 33 (150 μL) and solution 34 (150 μL) were fully stirred to obtain a primary hydrogel, and solution 35 (30 μL) was added to the surface of the primary hydrogel obtained in this example and allowed to stand at room temperature to obtain a three-component double-reaction hydrogel.

[0188] Embodiment 33

[0189] The 4-arm PEG-FA (100 mg) prepared in Example 1 was dissolved in PBS solution (1 mL) to obtain solution 36; the 4-arm PEG-CA (100 mg) prepared in Example 5 was dissolved in PBS solution (1 mL) to obtain solution 37; N-acetylcysteine ​​(Mn: 164 g / mol, 8.2 mg) was dissolved in PBS (1 mL) to obtain solution 38; solution 36 (150 μL) and solution 37 (150 μL) were fully stirred to obtain a primary hydrogel, and solution 38 (30 μL) was added to the surface of the primary hydrogel obtained in this example and allowed to stand at room temperature to obtain a three-component double-reaction hydrogel.

[0190] Embodiment 34

[0191] The 4-arm PEG-FA (100 mg) prepared in Example 1 was dissolved in PBS solution (1 mL) to obtain solution 39; the 4-arm PEG-CA (100 mg) prepared in Example 5 was dissolved in PBS solution (1 mL) to obtain solution 40; N-acetylcysteine ​​(Mn: 164 g / mol, 16.4 mg) was dissolved in PBS (1 mL) to obtain solution 41; solution 39 (150 μL) and solution 40 (150 μL) were fully stirred to obtain a primary hydrogel, and solution 41 (30 μL) was added to the surface of the primary hydrogel obtained in this example and allowed to stand at room temperature to obtain a three-component double-reaction hydrogel.

[0192] Embodiment 35

[0193] The 4-arm PEG-FA (100 mg) prepared in Example 1 was dissolved in PBS solution (1 mL) to obtain solution 42; the 4-arm PEG-CA (100 mg) prepared in Example 5 was dissolved in PBS solution (1 mL) to obtain solution 43; 3-mercaptopropionic acid (Mn: 106 g / mol, 10.6 mg) was dissolved in PBS (1 mL) to obtain solution 44; solution 39 (150 μL) and solution 40 (150 μL) were fully stirred to obtain a primary hydrogel, and solution 44 (30 μL) was added to the surface of the primary hydrogel obtained in this example and allowed to stand at room temperature to obtain a three-component double-reaction hydrogel.

[0194] Embodiment 36

[0195] The 4-arm PEG-FA (100 mg) prepared in Example 1 was dissolved in PBS solution (1 mL) to obtain solution 45; the 4-arm PEG-CA (100 mg) prepared in Example 5 was dissolved in PBS solution (1 mL) to obtain solution 46; thioglycolic acid (Mn: 92 g / mol, 9.2 mg) was dissolved in PBS (1 mL) to obtain solution 47; solution 45 (150 μL) and solution 46 (150 μL) were fully stirred to obtain a primary hydrogel, and solution 47 (30 μL) was added to the surface of the primary hydrogel obtained in this example and allowed to stand at room temperature to obtain a three-component double-reaction hydrogel.

[0196] Embodiment 37

[0197] The 8-arm PEG-FA (100 mg) prepared in Example 2 was dissolved in PBS solution (1 mL) to obtain solution 48; the 8-arm PEG-CA (100 mg) prepared in Example 6 was dissolved in PBS solution (1 mL) to obtain solution 49; N-acetylcysteine ​​(Mn: 164 g / mol, 16.4 mg) was dissolved in PBS (1 mL) to obtain solution 50; solution 48 (150 μL) and solution 49 (150 μL) were fully stirred to obtain a primary hydrogel, and solution 50 (30 μL) was added to the surface of the primary hydrogel obtained in this example and allowed to stand at room temperature to obtain a three-component double-reaction hydrogel.

[0198] Embodiment 38

[0199] Dex-FA (100 mg) prepared in Example 3 was dissolved in PBS solution (1 mL) to obtain solution 51; Dex-CA (100 mg) prepared in Example 7 was dissolved in PBS solution (1 mL) to obtain solution 52; N-acetylcysteine ​​(Mn: 164 g / mol, 16.4 mg) was dissolved in PBS (1 mL) to obtain solution 53; Solution 51 (150 μL) and solution 52 (150 μL) were fully stirred to obtain a primary hydrogel, and solution 53 (30 μL) was added to the surface of the primary hydrogel obtained in this example, and the mixture was allowed to stand at room temperature to obtain a three-component double-reaction hydrogel.

[0200] Embodiment 39

[0201] The HA-FA (100 mg) prepared in Example 4 was dissolved in PBS solution (1 mL) to obtain solution 54; the HA-CA (Mn: 100 mg) prepared in Example 8 was dissolved in PBS solution (1 mL) to obtain solution 55; N-acetylcysteine ​​(Mn: 164 g / mol, 16.4 mg) was dissolved in PBS (1 mL) to obtain solution 56; solution 54 (150 μL) and solution 55 (150 μL) were fully stirred to obtain a primary hydrogel, and solution 56 (30 μL) was added to the surface of the primary hydrogel obtained in this example, and allowed to stand at room temperature to obtain a three-component double-reaction hydrogel.

[0202] Embodiment 40

[0203] The three-component dual-reaction hydrogel prepared by Example 34 was freeze-dried and then characterized by scanning electron microscopy (SEM).

[0204] See also Figure 8 , Figure 8This is a scanning electron microscope (SEM) image of the three-component dual-reaction hydrogel prepared in Example 40 of the present invention. Figure 8 As shown, the hydrogel has a porous structure, and compared with the primary hydrogel prepared in Example 10, the hydrogel structure becomes denser.

[0205] Embodiment 41

[0206] The three-component dual-reaction hydrogels prepared by Example 10 and Examples 31 to 34 were transferred to a rotational rheometer to characterize their storage modulus and loss modulus.

[0207] See also Fig. 9 , Fig. 9 is the storage modulus and loss modulus of the three-component dual-reaction hydrogel of the present invention. Fig. 9 As shown, increasing the content of compounds containing thiol and carboxyl groups in the three-component dual-reaction hydrogel will enhance the mechanical strength of the hydrogel.

[0208] Embodiment 42

[0209] The three-component dual-reaction hydrogel prepared by the hydrogel of Example 10 and Example 34 were transferred to 5 mL glass bottles respectively. The mass of the hydrogel in each bottle was about 300 mg. 1 mL of PBS buffer solution with a pH of 7.4 was added to each bottle respectively. The bottles were cultured in a constant temperature incubator at 37°C. After all the PBS not absorbed by the hydrogel was sucked out at regular intervals, the weight of the hydrogel was weighed, and then new PBS (1 mL) was added again. This step was repeated until the hydrogel was completely dissolved.

[0210] See also Fig.10 , Fig.10 The degradation of the primary hydrogel prepared in Example 10 and the three-component double-reaction hydrogel prepared in Example 34 of the present invention in PBS is shown in FIG. Fig.10 As shown, the increase in the content of compounds containing thiol and carboxyl groups in the three-component dual-reaction hydrogel will prolong the degradation time of the primary hydrogel.

[0211] Embodiment 43

[0212] Mouse fibroblasts (L929) were inoculated in a sterile 96-well plate (8000 cells / well, 200 μL DMEM / well), and then placed in a sterile incubator for culture. After 24 h, the old culture medium was discarded, and 200 μL (n=5) of the three-component double-reaction hydrogel sample extract prepared in Example 34 of different concentrations were added to the wells. The extract was prepared by: 100 mg, 50 mg, 25 mg, 13 mg, 6.25 mg, 3.12 mg and 1.56 mg of the hydrogel prepared in Example 34 were soaked in 1 mL DMEM in a 5 mL glass bottle at 37 degrees Celsius for 24 h, and then the liquid was sucked out and filtered to obtain the extracts of the hydrogel samples prepared in Example 34 of different concentrations. The cell group cultured in DMEM was used as a control. After culturing for 24 h, the old culture medium was aspirated and 100 μL of 10% CCK-8 solution was added to each well. The cells were incubated in the incubator for 1 h, and then the absorbance of each sample well at 450 nm was detected using an enzyme-labeled instrument.

[0213] See also Fig.11 , Fig.11 The present invention provides a graph showing the cytotoxicity of the three-component dual-reaction hydrogel material to L929 cells at different concentrations. Fig.11 It can be seen that the experimental results show that the degradation products of hydrogels have no cytotoxicity to normal mouse fibroblasts, proving that hydrogels can be used in the biological field.

[0214] Embodiment 44

[0215] Mouse fibroblasts (L929) were inoculated in a sterile 96-well plate (8000 cells / well, 200 μL DMEM / well), and then placed in a sterile incubator for culture. After 24 h, the old culture medium was discarded, and 200 μL (n=5) of the three-component double-reaction hydrogel sample extract prepared in Example 37 of different concentrations were added to the wells. The extract was prepared by: 100 mg, 50 mg, 25 mg, 13 mg, 6.25 mg, 3.12 mg and 1.56 mg of the hydrogel prepared in Example 37 were soaked in 1 mL DMEM in a 5 mL glass bottle at 37 degrees Celsius for 24 h, and then the liquid was sucked out and filtered to obtain the extracts of the hydrogel samples prepared in Example 37 of different concentrations. The cell group cultured in DMEM was used as a control. After 24 hours of culture, the old culture medium was aspirated and 100 μL of 10% CCK-8 solution was added to each well. The cells were incubated in the incubator for 1 hour, and then the absorbance value of each sample well at 450 nm was detected by a microplate reader. The results showed that the degradation products of the hydrogel had no cytotoxicity to normal mouse fibroblasts, proving that the hydrogel can be used in the biological field.

[0216] Embodiment 45

[0217] Mouse fibroblasts (L929) were inoculated in a sterile 96-well plate (8000 cells / well, 200 μL DMEM / well), and then placed in a sterile incubator for culture. After 24 h, the old culture medium was discarded, and 200 μL (n=5) of the three-component double-reaction hydrogel sample extract prepared in Example 38 of different concentrations were added to the wells. The extract was prepared by: 100 mg, 50 mg, 25 mg, 13 mg, 6.25 mg, 3.12 mg and 1.56 mg of the hydrogel prepared in Example 38 were soaked in 1 mL DMEM in a 5 mL glass bottle at 37 degrees Celsius for 24 h, and then the liquid was sucked out and filtered to obtain the extracts of the hydrogel samples prepared in Example 38 of different concentrations. The cell group cultured in DMEM was used as a control. After 24 hours of culture, the old culture medium was aspirated and 100 μL of 10% CCK-8 solution was added to each well. The cells were incubated in the incubator for 1 hour, and then the absorbance value of each sample well at 450 nm was detected by a microplate reader. The results showed that the degradation products of the hydrogel had no cytotoxicity to normal mouse fibroblasts, proving that the hydrogel can be used in the biological field.

[0218] Embodiment 46

[0219] Mouse fibroblasts (L929) were inoculated in a sterile 96-well plate (8000 cells / well, 200 μL DMEM / well), and then placed in a sterile incubator for culture. After 24 h, the old culture medium was discarded, and 200 μL (n=5) of the three-component double-reaction hydrogel sample extract prepared in Example 39 of different concentrations were added to the wells. The extract was prepared by soaking 100 mg, 50 mg, 25 mg, 13 mg, 6.25 mg, 3.12 mg and 1.56 mg of the hydrogel prepared in Example 39 in 1 mL DMEM in a 5 mL glass bottle at 37 degrees Celsius for 24 h, then the liquid was aspirated and filtered to obtain the extracts of the hydrogel samples prepared in Example 39 of different concentrations. The cell group cultured in DMEM was used as a control. After 24 hours of culture, the old culture medium was aspirated and 100 μL of 10% CCK-8 solution was added to each well. The cells were incubated in the incubator for 1 hour, and then the absorbance value of each sample well at 450 nm was detected by a microplate reader. The results showed that the degradation products of the hydrogel had no cytotoxicity to normal mouse fibroblasts, proving that the hydrogel can be used in the biological field.

[0220] Embodiment 47

[0221] Mouse fibroblasts (L929) were inoculated on a 96-well culture plate at a density of 2000 cells / well, and 200 μL DMEM was added, and then placed in a sterile incubator for culture. After 24 hours, it was recorded as day 0; the old culture medium was discarded, and 200 μL (n=5) of the three-component double-reaction hydrogel sample extract prepared in Example 34 of different concentrations were added to the wells respectively. The extract was prepared by soaking 50 mg, 25 mg and 13 mg of the hydrogel prepared in Example 34 in 1 mL DMEM in a 5 mL glass bottle at 37 degrees Celsius for 24 hours, and then the liquid was sucked out respectively, and the extract of the hydrogel sample prepared in Example 34 of different concentrations was obtained by filtration. The cell group that continued to be cultured with DMEM was used as a control and continued to be cultured. On day 0, day 1, and day 3, the old culture medium was aspirated, and 100 μL of 10% CCK-8 solution was added to each well. The cells were incubated in the incubator for 1 h, and then the absorbance of each sample well at 450 nm was detected using a microplate reader.

[0222] See also Fig.12 , Fig.12 The invention provides a graph of the proliferation of L929 cells in a three-component dual-reaction hydrogel material of different concentrations;

[0223] The results are as follows Fig.12As shown, L929 cells can rapidly proliferate in the environment of the three-component dual-reaction hydrogel material provided by the present invention, proving that the hydrogel can be used in cell transplantation.

[0224] Embodiment 48

[0225] Mouse fibroblasts (L929) were inoculated on a 96-well culture plate at a density of 2000 cells / well, and 200 μL DMEM was added, and then placed in a sterile incubator for culture. After 24 hours, it was recorded as day 0; the old culture medium was discarded, and 200 μL (n=5) of the three-component double-reaction hydrogel sample extract prepared in Example 37 of different concentrations were added to the wells respectively. The extract was prepared by soaking 50 mg, 25 mg and 13 mg of the hydrogel prepared in Example 37 in 1 mL DMEM in a 5 mL glass bottle at 37 degrees Celsius for 24 hours, and then the liquid was sucked out respectively, and the extract of the hydrogel sample prepared in Example 37 of different concentrations was obtained by filtration. The cell group that continued to be cultured with DMEM was used as a control and continued to be cultured. On the 0th day, the 1st day and the 3rd day, the old culture medium was aspirated, and 100 μL of 10% CCK-8 solution was added to each well again, and the cells were incubated in the incubator for 1 h, and then the absorbance value of each sample well at 450 nm was detected by a microplate reader. The results showed that L929 cells could proliferate rapidly in the environment of the three-component dual-reaction hydrogel material provided by the present invention, proving that the hydrogel can be used in cell transplantation.

[0226] Embodiment 49

[0227] Mouse fibroblasts (L929) were inoculated on a 96-well culture plate at a density of 2000 cells / well, and 200 μL DMEM was added, and then placed in a sterile incubator for culture. After 24 hours, it was recorded as day 0; the old culture medium was discarded, and 200 μL (n=5) of the three-component double-reaction hydrogel sample extract prepared in Example 38 of different concentrations were added to the wells respectively. The extract was prepared by: 50 mg, 25 mg and 13 mg of the hydrogel prepared in Example 38 were soaked in 1 mL DMEM in a 5 mL glass bottle at 37 degrees Celsius for 24 hours, and then the liquid was sucked out respectively, and the extract of the hydrogel sample prepared in Example 38 of different concentrations was obtained by filtration. The cell group that continued to be cultured with DMEM was used as a control and continued to be cultured. On day 0, day 1, and day 3, the old culture medium was aspirated, and 100 μL of 10% CCK-8 solution was added to each well, and the cells were incubated in the incubator for 1 h. The absorbance of each sample well at 450 nm was then detected using a microplate reader. The results showed that L929 cells could rapidly proliferate in the environment of the three-component dual-reaction hydrogel material provided by the present invention, proving that the hydrogel can be used in cell transplantation.

[0228] Embodiment 50

[0229] Mouse fibroblasts (L929) were inoculated on a 96-well culture plate at a density of 2000 cells / well, and 200 μL DMEM was added, and then placed in a sterile incubator for culture. After 24 hours, it was recorded as day 0; the old culture medium was discarded, and 200 μL (n=5) of the three-component double-reaction hydrogel sample extract prepared in Example 39 of different concentrations were added to the wells respectively. The extract was prepared by soaking 50 mg, 25 mg and 13 mg of the hydrogel prepared in Example 39 in 1 mL DMEM in a 5 mL glass bottle at 37 degrees Celsius for 24 hours, and then the liquid was sucked out respectively, and the extract of the hydrogel sample prepared in Example 39 of different concentrations was obtained by filtration. The cell group that continued to be cultured with DMEM was used as a control and continued to be cultured. On the 0th day, the 1st day and the 3rd day, the old culture medium was aspirated, and 100 μL of 10% CCK-8 solution was added to each well again, and the cells were incubated in the incubator for 1 h, and then the absorbance value of each sample well at 450 nm was detected by a microplate reader. The results showed that L929 cells could proliferate rapidly in the environment of the three-component dual-reaction hydrogel material provided by the present invention, proving that the hydrogel can be used in cell transplantation.

[0230] Embodiment 51

[0231] PBS was used to mix mouse fibroblasts (L929) cells to prepare a cell suspension with a density of 50,000 cells / mL. 1 mL of PBS cell suspension containing mouse fibroblasts (L929) was first mixed with 50 mg of 4-armPEG-FA prepared in Example 1. After mixing evenly, 50 mg of 4-armPEG-CA prepared in Example 5 was further mixed to obtain a hydrogel precursor mixture. The hydrogel precursor mixture was then transferred to a 1 mL insulin syringe equipped with a 29G needle to form a primary hydrogel containing L929 cells. The primary hydrogel containing cells was injected into a 32-well culture plate at a flow rate of 1 mL / min to obtain a primary hydrogel containing cells after injection; N-acetylcysteine ​​(Mn: 164 g / mol, 16.4 mg) was dissolved in PBS (1 mL) to obtain solution 57. Solution 57 (20 μL) (n=3) was added to the surface of the primary hydrogel containing cells after injection obtained in this example.

[0232] 200 μL of the PBS cell suspension prepared in this example was injected into a 32-well culture plate at a flow rate of 1 mL / min using a 1 mL insulin syringe equipped with a 29G needle as a control group (n=3).

[0233] 200 μL (n=3) of the L929 cell hydrogel precursor mixture obtained in this example was transferred (not injected) to a 32-well plate, and after being placed, a primary hydrogel encapsulating L929 cells was formed, and then solution 57 (20 μL) (n=3) was added to the surface; at the same time, 200 μL (n=3) of the PBS cell suspension obtained in this example was also transferred (not injected) to a 32-well plate as a control.

[0234] 20 minutes after the injection and transfer, 1 mL of 10% CCK-8 solution was added to each well and incubated in the incubator for another 2 h. Then, 100 μL of liquid was aspirated from each well (n=5) into a 96-well plate and the absorbance of each sample well at 450 nm was detected using a microplate reader.

[0235] The results are as follows Fig.13 As shown, Fig.13 This is a characterization diagram of the protective effect of the three-component dual-reaction hydrogel of the present invention on encapsulated cells during the injection process; the results show that compared with direct use of PBS injection, the use of injectable three-component dual-reaction hydrogel can significantly improve the cell survival rate of internally encapsulated cells during injection, improve the efficiency of cell transplantation, and can be used as a cell transplantation carrier.

[0236] Embodiment 52

[0237] PBS was used to mix mouse fibroblasts (L929) cells to prepare a cell suspension with a density of 50,000 cells / mL. 1 mL of PBS cell suspension containing mouse fibroblasts (L929) was first mixed with 50 mg of 8-armPEG-FA prepared in Example 2. After mixing evenly, 50 mg of 8-armPEG-CA prepared in Example 6 was further mixed to obtain a hydrogel precursor mixture. The hydrogel precursor mixture was then transferred to a 1 mL insulin syringe equipped with a 29G needle to form a primary hydrogel containing L929 cells. The primary hydrogel containing cells was injected into a 32-well culture plate at a flow rate of 1 mL / min to obtain a primary hydrogel containing cells after injection; N-acetylcysteine ​​(Mn: 164 g / mol, 16.4 mg) was dissolved in PBS (1 mL) to obtain solution 58. Solution 58 (20 μL) (n=3) was added to the surface of the primary hydrogel containing cells after injection obtained in this example. The PBS cell suspension prepared in this example was injected into a 32-well culture plate at a flow rate of 1 mL / min using a 1 mL insulin syringe equipped with a 29G needle, 200 μL as a control group (n=3); 200 μL (n=3) of the L929 cell hydrogel precursor mixture obtained in this example was transferred (not injected) to a 32-well plate, and after being placed, a primary hydrogel containing L929 cells was formed, and then solution 58 (20 μL) (n=3) was added to the surface; at the same time, 200 μL (n=3) of the PBS cell suspension obtained in this example was also transferred (not injected) to a 32-well plate as a control. 20 minutes after the injection and transfer, 1 mL of a 10% CCK-8 solution was added to each well, and the cells were incubated in the incubator for 2 h, and then 100 μL (n=5) of the liquid was aspirated from each well into a 96-well plate, and the absorbance value of each sample well at 450 nm was detected using an ELISA reader.

[0238] The results show that the use of injectable three-component dual-reaction hydrogel can significantly improve the cell survival rate of internally encapsulated cells during injection, improve the efficiency of cell transplantation, and can be used as a cell transplantation carrier.

[0239] Embodiment 53

[0240] PBS was used to mix mouse fibroblasts (L929) cells to prepare a cell suspension with a density of 50,000 cells / mL. 1 mL of PBS cell suspension containing mouse fibroblasts (L929) was first mixed with 50 mg of Dex-FA prepared in Example 3. After mixing evenly, 50 mg of Dex-CA prepared in Example 7 was further mixed to obtain a hydrogel precursor mixture. The hydrogel precursor mixture was then transferred to a 1 mL insulin syringe equipped with a 29G needle to form a primary hydrogel containing L929 cells. The primary hydrogel containing cells was injected into a 32-well culture plate at a flow rate of 1 mL / min to obtain a primary hydrogel containing cells after injection; N-acetylcysteine ​​(Mn: 164 g / mol, 16.4 mg) was dissolved in PBS (1 mL) to obtain solution 59. Solution 59 (20 μL) (n=3) was added to the surface of the primary hydrogel containing cells after injection obtained in this example. The PBS cell suspension prepared in this example was injected into a 32-well culture plate at a flow rate of 1 mL / min using a 1 mL insulin syringe equipped with a 29G needle, 200 μL as a control group (n=3); 200 μL (n=3) of the L929 cell hydrogel precursor mixture obtained in this example was transferred (not injected) to a 32-well plate, and after being placed, a primary hydrogel containing L929 cells was formed, and then solution 59 (20 μL) (n=3) was added to the surface; at the same time, 200 μL (n=3) of the PBS cell suspension obtained in this example was also transferred (not injected) to a 32-well plate as a control. 20 minutes after the injection and transfer, 1 mL of a 10% CCK-8 solution was added to each well, and the cells were incubated in the incubator for 2 h, and then 100 μL (n=5) of the liquid was aspirated from each well into a 96-well plate, and the absorbance value of each sample well at 450 nm was detected using an ELISA reader.

[0241] The results show that the use of injectable three-component dual-reaction hydrogel can significantly improve the cell survival rate of internally encapsulated cells during injection, improve the efficiency of cell transplantation, and can be used as a cell transplantation carrier.

[0242] Embodiment 54

[0243] PBS was used to mix mouse fibroblasts (L929) cells to prepare a cell suspension with a density of 50,000 cells / mL. 1 mL of PBS cell suspension containing mouse fibroblasts (L929) was first mixed with 50 mg of HA-FA prepared in Example 4. After mixing evenly, 50 mg of HA-CA prepared in Example 8 was further mixed to obtain a hydrogel precursor mixture. The hydrogel precursor mixture was then transferred to a 1 mL insulin syringe equipped with a 29G needle to form a primary hydrogel containing L929 cells. The primary hydrogel containing cells was injected into a 32-well culture plate at a flow rate of 1 mL / min to obtain a primary hydrogel containing cells after injection; N-acetylcysteine ​​(Mn: 164 g / mol, 16.4 mg) was dissolved in PBS (1 mL) to obtain a solution 60, and a solution 60 (20 μL) (n=3) was added to the surface of the primary hydrogel containing cells after injection obtained in this example. The PBS cell suspension prepared in this example was injected into a 32-well culture plate at a flow rate of 1 mL / min using a 1 mL insulin syringe equipped with a 29G needle, 200 μL as a control group (n=3); 200 μL (n=3) of the L929 cell hydrogel precursor mixture obtained in this example was transferred (not injected) to a 32-well plate, and after being placed, a primary hydrogel containing L929 cells was formed, and then 60 (20 μL) of the solution was added to the surface (n=3); at the same time, 200 μL (n=3) of the PBS cell suspension obtained in this example was also transferred (not injected) to a 32-well plate as a control. 20 minutes after the injection and transfer, 1 mL of a 10% CCK-8 solution was added to each well, and the cells were incubated in the incubator for 2 h, and then 100 μL (n=5) of the liquid was aspirated from each well into a 96-well plate, and the absorbance value of each sample well at 450 nm was detected using an ELISA reader.

[0244] The results show that the use of injectable three-component dual-reaction hydrogel can significantly improve the cell survival rate of internally encapsulated cells during injection, improve the efficiency of cell transplantation, and can be used as a cell transplantation carrier.

[0245] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A three-component dual-reaction hydrogel material, characterized in that: Formed by cross-linking the first component, the second component and the third component; The first component is selected from one or more structures represented by formula (I-1) to formula (I-4): wherein m, n, o, p, d, z are the number of repeating units, m and n are each independently an integer of 10 to 100, and o, p, d and z are each independently an integer of 20 to 300; The second component is selected from one or more structures represented by formula (II-1) to formula (II-4): wherein z, g, e, q, j and h are the number of repeating units, z and g are each independently an integer of 10 to 100, and e, q, j and h are each independently an integer of 20 to 300; The third component is selected from one or more structures represented by formula (III-1) to formula (III-3): The mass ratio of the first component to the second component is 1:(0.1-10); The mass ratio of the third component to the first component or the second component is 1:(3-320); The preparation method of the three-component double-reaction hydrogel material comprises the following steps: S1) providing a solution of a first component; providing a solution of a second component; providing a solution of a third component; S2) mixing the solution of the first component with the solution of the second component to perform a cross-linking reaction to obtain a primary hydrogel; S3) adding a solution of a third component to the primary hydrogel to obtain a three-component double-reaction hydrogel material.

2. The hydrogel material according to claim 1, characterized in that The concentration of the first component in the solution of the first component is 20 to 200 mg / mL; The concentration of the second component in the solution of the second component is 20 to 200 mg / mL; The concentration of the third component in the solution of the third component is 1.64 to 16.4 mg / mL; The solvents of the solution of the first component, the solution of the second component and the solution of the third component are independently selected from one or more of water, physiological saline and buffer solution.

3. Use of the three-component dual-reaction hydrogel material according to any one of claims 1 to 2 in the preparation of a cell transplantation therapy carrier.

Citation Information

Patent Citations

  • Thiol-aldehyde group cross-linked hydrogel material, preparation method and applications thereof

    CN110128682A

  • Preparation method of hyaluronic acid-based bi-crosslinked hydrogel

    CN111303459A